Insights into Biofilm Dispersal Regulation from the Crystal Structure of the PAS-GGDEF-EAL Region of RbdA from Pseudomonas aeruginosa - Liu, Chong (2018)
RbdA is a positive regulator of biofilm dispersal of Pseudomonas aeruginosa. Its cytoplasmic region (cRbdA) comprises an N-terminal Per-ARNT-Sim (PAS) domain followed by a diguanylate cyclase (GGDEF) domain and an EAL domain, whose phosphodiesterase activity is allosterically stimulated by GTP binding to the GGDEF domain. We report crystal structures of cRbdA and of two binary complexes: one with GTP/Mg2+ bound to the GGDEF active site and one with the EAL domain bound to the c-di-GMP substrate. These structures unveil a 2-fold symmetric dimer stabilized by a closely packed N-terminal PAS domain and a noncanonical EAL dimer. The autoinhibitory switch is formed by an α-helix (S-helix) immediately N-terminal to the GGDEF domain that interacts with the EAL dimerization helix (α6-E) of the other EAL monomer and maintains the protein in a locked conformation. We propose that local conformational changes in cRbdA upon GTP binding lead to a structure with the PAS domain and S-helix shifted away from the GGDEF-EAL domains, as suggested by small-angle X-ray scattering (SAXS) experiments. Domain reorientation should be facilitated by the presence of an α-helical lever (H-helix) that tethers the GGDEF and EAL regions, allowing the EAL domain to rearrange into an active dimeric conformation.